Predictive Model on Limit Extension of Horizontal Well Drilling with Riserless Mud Recovery for Gas Hydrates in Offshore Areas - Jing Li; Bin Li; Bo Ning; Lujun Wang; Kaixiang Shen; Dongyu Yang; Xiaopeng Yan; Dezhi Qiu; Bin Zhu; Yanjiang Yu; Pengxiang Shen (Journal of Marine Science and Engineering, 2026)
Natural gas hydrate is an important emerging strategic resource, but low permeability makes the horizontal well length a key factor limiting productivity. A prediction model for friction torque of deepwater riserless drilling strings was established, and the segmented friction coefficient of hydrate horizontal wells was inverted and applied to the Shenhu hydrate reservoir. The results show that the main limiting factor for the extreme extension length of natural gas hydrate horizontal wells is the mechanical extreme extension length. The main affecting factor of the mechanical extreme extension length is the running limit of the screen pipe. The friction coefficient is the most significant factor affecting the mechanical extreme extension of horizontal wells, with the friction coefficient inside the casing in the high-build-rate section being the largest. The research identifies the primary factors governing the limit extension during horizontal well construction. The findings provide theoretical guidance for reservoir selection, well site determination, and wellbore configuration optimization in hydrate development. Ultimately, this contributes to maximizing single-well productivity and advancing the commercialization of hydrate resources.